Explorando as competências necessárias na jornada do Gerente de Produto - ABREU, Lucas Reis (2025)
The role of the Software Product Manager varies across organizations, but many of the challenges faced and the skills required are recurrent. This research aimed to map the main responsibilities and skills associated with this role, based on the common challenges encountered in software development. Additionally, it sought to distinguish the responsibilities of the Product Manager from those of the Product Owner and the Project Manager, roles that are often confused or overlap in organizational context. The methodology included a tertiary study of literature, followed by the design and application of interviews and questionnaires with professionals in the field. As a result, 107 competencies were identified and organized from 18 key challenges. Furthermore, elements were proposed to clarify the distinctions between the three analyzed roles. This research contributes to a better understanding of the Product Manager’s journey, offering theoretical and practical insights for their training and practice.